Demonstration of antibiotic-induced tolerance development in tropical agroecosystems through physiological profiling of sediment microbial communities - Arias Andrés, María de Jesús (2014)
Agricultural use of antibiotics differs quantitatively and qualitatively in tropical and temperate countries. To gain insight into the nature and magnitude of physiological adaptations prompted by these drugs in microbial communities from tropical agroecosystems, we compared community-level physiological profiles of sediment bacteria from a protected wetland (PV), a pig farm (RD), treated (TIL1) and untreated effluents (TIL2) from a tilapia farm, an estuary close to shrimp farms (CA), and an irrigation channel adjacent to a rice plantation (AZ) exposed to a range of oxytetracycline (OTC) concentrations in Ecoplates (Biolog®). In addition, we used LC/MS/MS and plate counts to determine the concentration of OTC and the number of OTC-resistant bacteria in the samples, respectively. Water samples collected at RD contained maximum amounts of OTC (640 ng L-1), followed by TIL2 (249 ng L-1), TIL1 (72 ng L-1), and CA (85 ng L-1). In average, the microbial community of RD was more tolerant to OTC (EC50: 14.30 ± 3.12 mg L-1) than bacteria from CA (8.83 ± 1.85 mg Ll-1), TIL2 (EC50: 4.97 ± 1.43 mg L-1), TIL1 (4.25 ± 0.60 mg L-1), AZ (3.66 ± 0.97 mg L-1) and PV (3.77 ± 0.62 mg L-1). Congruently, PV, AZ, TIL1, CA, TIL2, and RD appeared in that order in a cumulative distribution of individual EC50 values and higher plate counts of bacteria resistant to 10 µg mL-1 (5.0x105- 1.5x107) and 100 µg mL-1 of OTC (1.5x104-8.4x105) were obtained for RD than for the other sites (10 µg ml-1: 4.8x104-3.3x105 and 100 µg mL-1: 1.0x102-4.4x103). These results are compatible with a scenario in which the basal level of tolerance to OTC that characterizes pristine environments (PV) is amplified in proportion to the intensity of antibiotic exposure (agriculture<aquaculture<swine farming).